Predicting pulmonary tuberculosis in immigrants: a retrospective cohort study. Issue 2 (20th April 2018) - Heffernan, Courtney; Doroshenko, Alexander; Egedahl, Mary Lou; Barrie, James; Senthilselvan, Ambikaipakan; Long, Richard
Our objective was to investigate whether pulmonary tuberculosis (PTB) can be predicted from features of a targeted medical history and basic laboratory investigations in immigrants. A retrospective cohort of 391 foreign-born adults referred to the Edmonton Tuberculosis Clinic (Edmonton, AB, Canada) was studied using multiple logistic regression analysis to predict PTB. Seven characteristics of disease were used as explanatory variables. Cross-validation assessed performance. Each predictor was tested on two outcomes: "culture-positive" and "smear-positive". Receiver operating characteristic (ROC) curves were generated and the area under the ROC curve (AUC) was quantified. Symptoms, subacute duration of symptoms, risk factors for reactivation of latent TB infection and anaemia were all associated with a positive culture (adjusted OR 1.79, 2.24, 1.72 and 2.28, respectively; p<0.05). Symptoms, inappropriate prescription of broad-spectrum antibiotics and a "typical" chest radiograph were associated with smear-positive PTB (adjusted OR 2.91, 1.55 and 12.34, respectively; p<0.05). ROC curve analysis was used to test each model, yielding AUC=0.91 for the outcome "culture-positive" disease and AUC=0.94 for the outcome "smear-positive" disease. PTB among the foreign-born can be predicted from a targeted medical history and basic laboratory investigations, raising the threshold of suspicion in settings where the disease is relatively rare. In high-income, low tuberculosis incidence countries, certain clinical characteristics should raise the threshold of suspicion to confirm a timely diagnosis http://ow.ly/bRDZ30iPurz